Investment in shares: basic principles in fundamental and technical analysis / Md Johari Abdul Jalil - Abdul Jalil, Md Johari (1988)
This project paper is carried out in part four as part of the ACC 555 subject and a time of five months is given to complete the project. At the same time the student is required to go on a practical training for the same duration. The students are given the freedom to propose the topic of the their project paper and subsequently approved by the advicer. The topic for my project is INVESTMENT IN SHARES : THE BASIC OF FUNDAMENTAL AND TECHNICAL ANALYSIS. I choosed this topic because it is related to accounting and also as part of my preparation for Financial Management subject which I will encounter in part 5.